The exact S-matrices of the principal chiral model with any non-exceptional symmetry group - Abdalla, M. C.B. (Elsevier, 1985)
Using the conservation of the quantum non-local charge, the S-matrices of pure non-linear sigma models with symmetry G ⊗ G (G non-exceptional) are computed. © 1985.